Rozwiązane

Oblicz wyrażenia podane poniżej, jeżeli A = 4x^2 – 2xy + 6 B = – 4x^2 + 4xy – 6

A + B

0,5B – A

5A – 3B​



Odpowiedź :

A + B

(4x^2-2xy + 6) + (-4X^2+4xy-6) = 4x^2 - 2xy + 6 - 4x^2+4xy - 6 = -2xy + 6 + 4xy - 6 = -2xy + 4xy = 2xy

0,5B - A

0,5 * (-4X^2+4xy-6) - (4x^2-2xy + 6) = -2x^2 + 2xy - 3 - 4x^2 + 2xy - 6 = -6x^2 + 4xy - 3 - 6 = -6x^2 + 4xy - 9

5A - 3B

5 * (4x^2-2xy + 6) - 3 * (-4X^2+4xy-6) = 20x^2 - 10xy + 30 + 12x^2 - 12xy + 18 = 32x^2 - 22xy + 30 + 18 = 32x^2 - 22xy + 48